2006
DOI: 10.1128/mcb.01155-06
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of Interleukin-6 mRNA Requires a Putative RNA Stem-Loop Structure, an AU-Rich Element, and the RNA-Binding Protein AUF1

Abstract: Interleukin-6 mRNA is unstable and degraded with a half-life of 30 min. Instability determinants can entirely be attributed to the 3 untranslated region. By grafting segments of this region to stable green fluorescent protein mRNA and subsequent scanning mutagenesis, we have identified two conserved elements, which together account for most of the instability. The first corresponds to a short noncanonical AU-rich element. The other, 80 nucleotides further 5, comprises a sequence predicted to form a stem-loop s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(150 citation statements)
references
References 76 publications
9
135
2
Order By: Relevance
“…In his review, Pestka (2008) summarised the genes with a lower mRNA decay rate upon DON administration, which are COX-2, tumour necrosis factor (TNF)-a and interleukin (IL)-6 in macrophages and IL-2 in EL-4T-cells. It has been reported that all four mRNAs are stabilised by ARE in the 3 0 untranslated region (Chen et al, 2001, Paschoud et al, 2006, Rajasingh et al, 2006. The downregulation of EXOSC9 and XRN1 might be the reason for increased mRNA stability of several ARE-containing genes in DON-challenged cell cultures.…”
Section: Translation Initiationmentioning
confidence: 95%
“…In his review, Pestka (2008) summarised the genes with a lower mRNA decay rate upon DON administration, which are COX-2, tumour necrosis factor (TNF)-a and interleukin (IL)-6 in macrophages and IL-2 in EL-4T-cells. It has been reported that all four mRNAs are stabilised by ARE in the 3 0 untranslated region (Chen et al, 2001, Paschoud et al, 2006, Rajasingh et al, 2006. The downregulation of EXOSC9 and XRN1 might be the reason for increased mRNA stability of several ARE-containing genes in DON-challenged cell cultures.…”
Section: Translation Initiationmentioning
confidence: 95%
“…The AREs allow rapid mRNA degradation by promoting the recruitment of mRNA-destabilizing proteins to the 3"UTR. The IL-6 3"UTR contains six AREs [8]. In several systems, IL-6 has been described to have a short half life, varying from 30 minutes [8][9][10]] to 50 minutes [11].…”
Section: Introductionmentioning
confidence: 99%
“…The IL-6 3"UTR contains six AREs [8]. In several systems, IL-6 has been described to have a short half life, varying from 30 minutes [8][9][10]] to 50 minutes [11]. Several extracellular stimuli have been described to have a stabilizing effect on IL-6 mRNA, such as IL-1β [9,12]; IL-17 [13,14];…”
Section: Introductionmentioning
confidence: 99%
“…The structure of an RNA hairpin depends on several parameters, such as loop size, stem length and the number of bulges, among others (Svoboda and di Kara, 2006). It has been reported that RNA hairpins can regulate stability, translation and localization of its target mRNA, as was shown for the ARE-containing interleukin-6 and c-myc transcripts (Chabanon et al, 2005;Paschoud et al, 2006). As a consequence, it is generally accepted that the functionality of AREs depends on different ARE-BPs and additionally on sequence accessibility.…”
Section: Discussionmentioning
confidence: 99%